Edukasi Tentang Pertolongan Pertama Pada Kecelakaan (P3K): Balut Luka Desa Ledug Purwokerto - Savitri, Annistia Intan; Handayani, Rahmaya Nova; Wibowo, Tophan Heri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Background:First Aid for Accidents (P3K) is an action that can be given to treat victims as soon as possible at the scene before medical personel take over the treatment. First aid for accidents in the home environment is very helpful in minimizing the occurrence of infection in victims. Purpose :The purpose of implementing this community service is to determine the level knowledge of resident regarding first aid for wound dressing accidents. Methode: The Community Service method is by lecture and demonstration methods. There were 30 participants present. The activity was carried out in Ledug Village on Monday, Juli 29 2024 with media used, namely power point, leaflets, and audio vinni. Results : Results of Community service the level of knowledge before education was carried out was 25 participants (83,3%) had low knowledge, 5 participants (16.7%) had high knowledge. Meanwhile, after being given education, 25 participants (83,3%) had high knowledge and 5 participants (16.7%) had low knowledge. The skill level obtained from the pre-test skill results almost all participants did not have the skills as many as 28 participants (93.3%) while after being given a demonstration and audi visual the skill level increased to 15 participants (60%) and 12 participants (40%) had not had an increase. Consclusion: based on the results of the pre-test and post test percentages, the level of knowledge and skills that have been carried out showed an increase in the output of Journal of  Education on First Aid (P3K) balut luka.